Agreement on the perception of moral character - Helzer, Erik, G.; Furr, R. Michael; Hawkins, Ashley; Barranti, Maxwell; Blackie, Laura E.R.; Fleeson, William (SAGE, 2014)
This study tested for inter-judge agreement on moral character. A sample of students and community members rated their own moral character using a measure that tapped six moral character traits. Friends, family members, and/or acquaintances rated these targets on the same traits. Self/other and inter-informant agreement was found at the trait level for both a general character factor and for residual variance explained by individual moral character traits, as well as at the individual level (judges agreed on targets’ “moral character profiles”). Observed inter-judge agreement constitutes evidence for the existence of moral character, and raises questions about the nature of moral character traits.